2012
DOI: 10.1038/ajg.2012.347
|View full text |Cite
|
Sign up to set email alerts
|

Sedation in Screening Colonoscopy: Impact on Quality Indicators And Complications

Abstract: Sedation does not increase adenoma or polyp detection, although it leads to an increase in CIR in men and women. This effect is more pronounced in women, yet CIR of men remains higher compared with women. Quality indicators are mainly influenced by the patient's age, sex, and the endoscopists' individual performance, rather than the endoscopists' subspeciality or procedural experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 43 publications
6
66
0
Order By: Relevance
“…Evidence of sedation impact on polyp [48] or adenoma detection [49] is both limited and controversial [50]. Our study provides confirmation that sedation has no influence on adenoma detection [49,51].…”
Section: Discussionsupporting
confidence: 85%
“…Evidence of sedation impact on polyp [48] or adenoma detection [49] is both limited and controversial [50]. Our study provides confirmation that sedation has no influence on adenoma detection [49,51].…”
Section: Discussionsupporting
confidence: 85%
“…[6] The most common causes of incomplete colonoscopy are pain, stenosis, poor bowel preparation, low BMI, advanced age, gender (female), hysterectomy story, diverticulitis, inflammatory bowel disease, loop formation of the intestines, and complication during the procedure. [3,5,7] In our series, one of the three incomplete processes had hysterectomy story, and the other had loop formation. To increase CIR, various techniques such as water infusion and carbon dioxide insufflation, and also various device modifications like pediatric, robotic, double balloon, long or very thin colonoscopy usage have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in many countries, it is performed under either conscious or deep sedation. [10] In their very comprehensive study including more than 50,000 cases, Bannert et al [7] have shown that colonoscopy performed under sedation increased CIR in both men and women. Radaelli et al [11] reported that, CIR in colonoscopies with sedation and without sedation are in turn 84.2% and 76.1%.…”
Section: Discussionmentioning
confidence: 99%
“…8 Unfortunately, the increased burden on the health care system has not been associated with improvements in outcome in terms of colorectal cancer prevention. 9,10 Risks, cost, and practical inconveniences associated with the use of parenteral sedation warrant the development of orally administered, noncentrally acting colonic analgesic drugs. In this regard, an initial peripherally acting opioid agonist was evaluated for the management of visceral pain in patients undergoing full, sedation-free colonoscopy.…”
Section: Introductionmentioning
confidence: 99%